A comparison of the functional importance of pain expressions in the Wong-Baker and the FPS-R pain scales - Batalha, Luís Manuel da Cunha (2013)
Abstract title A comparison of the functional importance of pain expressions in the Wong-Baker and the FPS-R pain scales Background and aims One often raised issue about faces pain scales concerns the preference of children for one or another available scale. This work contends that an equally significant but different issue is the importance children accord to faces within a scale as expressive conveyers of pain. Methods Information Integration Theory methodology was used. The WB and FPS-R scales were taken as factors in a 6 x 6 integration task. Children judged overall pain expressed by pairs of faces using a continuous response dimension. Participants: 3 groups aged 6-8, undergoing distinct pain experiences (pain-free: n = 29; post-operatory: n = 17; chronic pain: n = 19); 3 corresponding groups aged 9-11: n = 32; n = 27; n = 22). Results Children in all groups used averaging to integrate the information conveyed by the pain faces. The weight/importance of the contribution of each face to the integrated judgment was estimated. Importance increased with level of intensity in both scales, but more so in the WB. Higher intensity expressions of the WB were found more important than those of the FPS, more so in the post-operatory groups. Lower intensity levels were in turn found more important in the FPS. Conclusions In the eyes of children, FPS offers a better representation of lower to moderate levels of pain, while WB does so for moderate to intensity levels. Differences in age and pain history did not affect this overall result. Acknowledgements Work supported by grant PTDC/PSI-PCO/107910/2008 - Portuguese Foundation for Science and Technology